Short-term methods for estimating the chronic toxicity of effluents and receiving waters to marine and estuarine organisms - Klemm, Donald J.; Morrison, George E; United States. Environmental Protection Agency. Office of Research and Development (Cincinnati, Ohio : United States Environmental Protection Agency, 1992)
10